Customer Engagement Through Instagram Quiz Content by BPJS Ketenagakerjaan - Aji, Arfanul; Ganiem, Leila Mona (Jurnal ICT : Information and Communication Technologies, 2025)
This study explores the effectiveness of Instagram-based interactive quizzes in enhancing public engagement with BPJS Ketenagakerjaan. Employing a quasi-qualitative method within a constructivist paradigm, the research investigates how quiz content contributes to user interaction, social security awareness, and audience comprehension. Data were collected through interviews, observations, and engagement rate (ER) analysis between quiz and non-quiz content in 2024. The findings show that quizzes significantly outperform non-quiz content in engagement, with the highest ER reaching 16.29% in October. Key factors influencing engagement include the relevance of quiz themes, interactivity, timing of posts, and incentive offerings. Interviews with six participants—comprising field workers, office employees, and academics—reveal that quizzes are seen as entertaining, informative, and motivating due to their rewards and interactive nature. Additionally, quizzes were found to enhance engagement across cognitive (understanding), affective (emotional connection), and behavioral (information-seeking) dimensions. Social-level effects were also observed, with participants sharing information from the quizzes, creating a ripple effect of public awareness. The study concludes that interactive Instagram quizzes are an effective digital communication strategy for increasing public engagement and understanding of BPJS Ketenagakerjaan’s programs. It recommends diversifying quiz formats, aligning content with trending topics, strengthening incentives, and incorporating follow-up engagement tools such as live Q&A sessions and discussion forums.